The Impact of Gadget Use on the Aspects of Early Childhood Language Development during Covid-19 - Vebionita Megi Putri; Delfi Eliza (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
Children are generations or descendants as a result of the relationship between men and women, whether in marriage or not. Early childhood is an individual who is experiencing a period of very rapid growth, even though now the entire world is experiencing the Covid-19 pandemic, it is not an obstacle to children's development and growth. With the pandemic, the government is implementing learning at home, the use of technology media is the main key in online learning. This study aims to describe the impact of using gadgets in early childhood in the aspects of language development. This research was conducted using the literature study method in which journals, books and other sources reinforce this research.